Spinal Hypotension and Time from Spinal-to-Delivery in Scheduled Cesarean Deliveries: Association with Neonatal Acidosis - Kazzi, Nayla G.; Chen, Han-Yang; Lee, Linden; Nazeer, Sarah A.; Brown, Kendra; Sibai, Baha M.; Chauhan, Suneet P. (American Journal of Perinatology, 2023)
Objective This work aimed to study the effect of sustained hypotension after spinal on neonatal acidosis and adverse outcomes in those undergoing scheduled cesarean delivery (CD) with universal prophylactic vasopressor exposure and to examine differences in spinal-to-delivery time by neonatal acidosis status.Study Design This retrospective cohort study conducted at a quaternary care center from January 2019 to December 2021 included singleton, term, nonanomalous pregnancies, with scheduled CD under spinal anesthesia. Hypotension was defined as a systolic blood pressure (SYS-BP) < 100 mm Hg (SYS-BP100) or a >20% drop from baseline blood pressure (SYS-BP20). Both the occurrence of hypotension and its magnitude and duration were studied; the latter through the development of a hypotension index. The 90th and 95th percentiles of the hypotension index for SYS-BP20 and SYS-BP100, respectively, were used to define sustained hypotension. The primary outcome was neonatal acidosis (umbilical artery pH ≤ 7.1 or base excess ≤ −12 mmol). Secondary outcomes were composites of neonatal (CNAO) and maternal (CMAO) adverse outcomes. Multivariable Poisson regression models with robust error variance analysis was used to estimate adjusted relative risks (aRRs) and 95% confidence intervals (CIs).Results Our study included 332 individuals who underwent scheduled CD; among them 330 (99.4%) received prophylactic vasopressors. The rate of neonatal acidosis was 4.2%. Sustained hypotension after spinal anesthesia, which occurred in 12.3% of the cohort, was associated with increased risk for neonatal acidosis (aRR 3.96, 95% CI 1.21–12.98), but was not associated with CNAO or CMAO. Time from spinal-to-delivery was not different in those with and without neonatal acidosis.Conclusion Despite universal exposure to prophylactic vasopressors, sustained hypotension after spinal anesthesia was still associated with neonatal acidosis, but no other adverse perinatal outcomes. Our findings may provide additional support for the adoption of prophylactic vasopressors to reduce spinal hypotension and downstream effects on the neonate from intraoperative hemodynamic instability.Key Points
Keywords: cesarean delivery; neonatal acidosis; vasopressors; spinal hypotension